ARTICLE TITLE: INTIMACY AND MARKET ON INSTAGRAM: RELATIONAL WORK AS A STRATEGY OF ECONOMIC DENIAL - Jardim, Maria Chaves [UNESP]; Di Pires, Luana Estela [UNESP]; Vasques, Lucas Flôres [UNESP] (FapUNIFESP (SciELO), 2024)
The aim of the article is to elucidate the intersection of intimacy and the market on the social network, ensuring that neither sphere contaminates the other. To achieve this, virtual ethnography was conducted, analyzing the posts of five influencers who monetize intimacy on the image-sharing platform, Instagram. Drawing on theoretical inspiration from Viviana Zelizer’s concepts, notably the theory of separate spheres, hostile worlds, and relational work, we contend that the monetization of intimacy by Instagram influencers is only possible due to its euphemized nature. In essence, influencers engage in significant relational work to mask the economic dimension, presenting their content as spontaneous and unpretentious, despite meticulous planning—a process made viable through Economic Denial. Maintaining symbolic boundaries between the spheres of intimacy and the market serves as a strategy for embracing the Instagram-driven market construction.
INTIMIDADE E MERCADO NO INSTAGRAM: TRABALHO RELACIONAL COMO ESTRATÉGIA DE DENEGAÇÃO DO ECONÔMICO
Keywords: Instagram; Intimacy; Market; Relational Work; Viviana Zelizer